The opinions and practices of providers toward the sexual issues of cervical cancer patients undergoing treatment - Bedell, Sarah; Manders, Dustin; Kehoe, Siobhan; Lea, Jayanthi; Miller, David; Richardson, Debra; Carlson, Matthew (Gynecologic oncology, 2017)
Cervical cancer and its treatments impair women's sexual function. These complications may or may not be regarded when clinicians develop treatment plans. We aim to investigate the considerations of providers toward the sex life of cervical cancer patients. All members of the Society of Gynecologic Oncology received a questionnaire assessing their opinions and practices toward specific questions regarding the sexual functioning of their patients. Of the 124 providers who completed the survey, the majority were Board Certified Gynecologic Oncologists (56%) with an average of 15years in training. Approximately 23% received training about sexual dysfunction. Providers without formal training were more likely to agree that: “Information regarding sexual function in patients undergoing treatment for cervical cancer is lacking” (p=0.02). Providers with over 10years of experience were more likely to agree that “sex is private and discussing it with patients will interfere with our provider-patient relationship” (p=0.03). International clinicians were more likely to agree that: “I feel uncomfortable initiating discussions regarding sexual function with patients” (p=0.03), “Sex is private and discussing it with patients will interfere in our provider-patient relationship” (p=0.02), and “If a patient has a sexual problem, they will raise the subject” (p=0.009). Years of clinical experience, provider age, a history of training on regarding sexual dysfunction and an international setting of practice affect providers' opinions and practices toward sexual issues of cervical cancer patients. More formal, relevant training regarding sexual dysfunction is warranted for clinicians who treat cervical cancer patients. •Most patients have sexual dysfunction, but few providers receive training in this.•Most providers want to receive more education about sexual dysfunction issues.•Non-trained providers agree that information on sexual dysfunction is lacking.•Despite a lack of training, most providers offer advice about sexual function.•International providers are more uncomfortable discussing sexual dysfunction.